Method for constructing high-activity gradient porous carbon nanofiber electrode material based on graphite microparticles and application of high-activity gradient porous carbon nanofiber electrode material in vanadium battery

Through electrospinning technology and heat treatment, a high-active gradient porous carbon nanofiber electrode material was prepared, which solved the problem of insufficient activity of vanadium battery electrode materials and the mass transfer performance of electrolytes, and significantly improved the electrochemical performance and energy conversion efficiency of vanadium battery cells. .

CN119121457APending Publication Date: 2024-12-13LIAONING UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311680409.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-08
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing vanadium battery electrode materials have poor electrochemical reactivity, and the low porosity of carbon nanofiber materials leads to poor mass transfer performance of the electrolyte, affecting battery performance.

Method used

Electrospinning technology is used to disperse graphite microparticle powder of different quality in polyacrylonitrile solution to form an electrospinning precursor solution with gradient distribution of graphite microparticle content. After electrospinning and heat treatment, high-active gradient porous carbon nanometers are prepared. The fiber electrode material, combined with preoxidation and carbonization, forms an electrode material with a gradient pore structure.

Benefits of technology

It improves the electrode reactive activity and electrolyte mass transfer efficiency, improves the electrochemical performance and energy conversion efficiency of vanadium batteries, and simplifies the preparation process, making it easy to operate and easy to regulate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004595978370000011
    Figure HDA0004595978370000011
  • Figure HDA0004595978370000012
    Figure HDA0004595978370000012
  • Figure HDA0004595978370000021
    Figure HDA0004595978370000021
Patent Text Reader

Abstract

The invention discloses a method for constructing a high-activity gradient porous carbon nanofiber electrode material based on graphite microparticles and application of the high-activity gradient porous carbon nanofiber electrode material in a vanadium battery. The method comprises the following steps: dispersing graphite microparticle powder with different masses into a mixed solution of PAN and DMF to prepare three electrospinning precursor solutions with different graphite powder contents; and carrying out continuous electrostatic spinning on the three electrospinning precursor solutions according to the size sequence of the content of the graphite powder by using an electrostatic spinning technology to obtain an original gradient structure composite fiber material, flattening the original gradient structure composite fiber material by using a corundum plate, and carrying out pre-oxidation and carbonization treatment in a tubular furnace to obtain the high-activity gradient porous carbon nanofiber electrode material. The surface containing more graphite particles in the material is in contact with a current collector, the surface containing less graphite particles is in contact with a diaphragm, and an all-vanadium redox flow battery is assembled, so that the mass transfer of an electrolyte in an electrode can be promoted while the electrochemical reaction activity of vanadium ions is improved, and the battery performance is further effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials and energy storage, and in particular to a method for constructing a highly active gradient porous carbon nanofiber electrode material based on graphite microparticles and an application thereof in a vanadium battery. Background Art

[0002] Efficient use of clean renewable energy and reduction of traditional energy such as oil are the keys to ensuring long-term energy supply, improving the human living environment, and achieving green sustainable development strategies. With the rapid development of renewable energy, the large-scale energy storage technology that matches it has also received widespread attention. Vanadium redox flow battery is one of the most industrially advantageous large-scale energy storage technologies. It has the advantages of easy expansion, long cycle life, high safety, fast response speed and large capacity, making it one of the preferred technologies for large-scale energy storage.

[0003] As the place where the electrochemical reaction of vanadium batteries occurs, the electrode directly affects the battery performance. At present, the most widely used flow battery electrode material is polyacrylonitrile-based carbon fiber material, which has the advantages of low cost, high conductivity and stable properties, but its electrochemical reaction activity is poor. In recent years, research on surface modification of carbon fiber materials and improving their electrochemical reaction activity for vanadium ions has attracted much attention. The commonly used methods are surface etching and catalyst modification. Using electrospinning technology, various functional components can be introduced into electrospun carbon nanofibers by designing the composition of the precursor solution to improve their reaction performance. However, due to the low porosity of carbon nanofiber materials, the flow resistance of the electrolyte in them is large, and the mass transfer performance is poor. How to promote the mass transfer of the electrolyte inside the electrode while improving the electrode reaction activity is crucial. During the charge and discharge process of vanadium batteries, the side close to the membrane is the active reaction area, so the electrode needs to have a higher active area on the side close to the diaphragm; the side close to the current collector is the fast mass transfer area, so the electrode needs to have a higher mass transfer rate on the side close to the current collector. Designing electrode materials with gradient pore structures and activities can effectively solve the above problems. Summary of the invention

[0004] One of the purposes of the present invention is to provide a method for constructing a highly active gradient porous carbon nanofiber electrode material based on graphite microparticles. The prepared electrode material has a gradient pore structure and activity.

[0005] The second purpose of the present invention is to provide a method for applying a highly active gradient porous carbon nanofiber electrode material constructed based on graphite microparticles in a vanadium battery.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for constructing a highly active gradient porous carbon nanofiber electrode material based on graphite microparticles, comprising the following steps:

[0007] 1) three graphite microparticle powders of different masses are dispersed in a mixed solution of polyacrylonitrile (PAN) and N,N,-dimethylformamide (DMF) to obtain three electrospinning precursor solutions with different graphite microparticle contents;

[0008] 2) electrospinning three electrospinning precursor solutions with different graphite microparticle contents continuously in the order of graphite microparticle contents from large to small or from small to large to obtain original nanofiber materials with a gradient distribution of graphite microparticle contents;

[0009] 3) The original nanofiber material with a gradient distribution of graphite microparticle content is flattened with a corundum plate, placed in a tubular furnace for pre-oxidation and carbonization treatment, and cooled to room temperature to obtain a high-activity gradient porous carbon nanofiber electrode material assembled from fiber layers with three different graphite microparticle contents.

[0010] Furthermore, in step 1), the diameter of the graphite particles is 1-2 μm, and the graphite particles in the three electrospinning precursor solutions with different contents of graphite particles are 0%, 0.1-0.2% and 1-2% by mass respectively.

[0011] Furthermore, in step 1), the molecular weight of polyacrylonitrile PAN is 90,000 to 150,000, and the concentration of polyacrylonitrile in the electrospinning precursor solutions with three different graphite microparticle contents is 10 to 20 wt % by mass.

[0012] Furthermore, in step 2), the conditions for electrospinning are as follows: the stainless steel nozzle model is G17~G22; the collector is a stainless steel roller, and the roller speed is 50~150r / min; the voltage between the nozzle and the roller is 19~22kV; the distance between the nozzle and the roller is 10~15cm; the spinning temperature is 25~35℃; the spinning humidity is 20~50%RH; the push speed is 20~40μL / min; the volume of each electrospinning precursor solution is 2~10mL.

[0013] Furthermore, in step 3), the pre-oxidation treatment conditions are: air atmosphere, heating rate of 1-5°C / min, pre-oxidation temperature of 260-320°C, and holding time of 30-120min.

[0014] Furthermore, in step 3), the carbonization treatment conditions are: under nitrogen or argon atmosphere, heating rate 1-5°C / min, carbonization temperature 900-1200°C, and holding time 60-180min.

[0015] The invention provides an application of a highly active gradient porous carbon nanofiber electrode material constructed based on graphite microparticles in an all-vanadium liquid flow battery.

[0016] Furthermore, the method is as follows: in a highly active gradient porous carbon nanofiber electrode material constructed based on graphite microparticles, a fiber layer with a high content of graphite microparticles is contacted with a current collector, and a fiber layer with a low content of graphite microparticles is contacted with a diaphragm to assemble an all-vanadium liquid flow battery.

[0017] Furthermore, in the all-vanadium liquid flow battery, the electrolyte flow rate is 15-50 mL / min, the vanadium ion concentration is 1.0-1.7 M, and the sulfuric acid supporting electrolyte concentration is 2.0-3.0 M.

[0018] Furthermore, the current collector is a graphite composite conductive plastic plate, and the diaphragm is a nafion212 proton exchange membrane.

[0019] The beneficial effects of the present invention are:

[0020] 1. The present invention utilizes simple and controllable electrospinning technology, combined with subsequent pre-oxidation and carbonization processes, to spin fiber layers of different looseness into an integrated composite carbon nanofiber layer, thereby obtaining an electrode material with gradient porous structure characteristics. The method is universal, and the fiber morphology can be adjusted according to the needs and characteristics of the electrochemical reaction to prepare highly active carbon nanofiber materials, and applied to specific electrode reactions, and is simple to operate and easy to control.

[0021] 2. The present invention constructs a highly active gradient porous carbon nanofiber electrode material based on graphite microparticles for use in the positive and negative electrodes of vanadium batteries, and the side containing more graphite particles is in contact with the current collector, and the side containing fewer graphite particles is in contact with the diaphragm. The symmetrically structured vanadium battery improves the electrode reaction kinetics of the vanadium battery while enhancing the transmission of active substances, thereby more effectively improving the battery's electrolyte utilization and energy conversion efficiency.

[0022] 3. The present invention achieves the supporting effect of graphite microparticles on carbon nanofibers by regulating the content of graphite microparticles in the polyacrylonitrile precursor solution, and simultaneously constructs a carbon nanofiber electrode material with a gradient pore structure and composition. The side with a low graphite particle content is used as an active reaction zone to provide a larger reaction area; the side with a high graphite particle content is used as a mass transfer enhancement zone to provide a lower mass transfer resistance. By using different masses of graphite powder and mixing them with the same mass of polyacrylonitrile PAN and N,N,-dimethylformamide, three electrospinning precursor solutions with different graphite powder contents are obtained; using electrospinning technology, the three electrospinning precursor solutions are continuously electrospun in order of graphite powder content to obtain the original composite fiber material, and after heat treatment, a vanadium battery electrode material with gradient porosity is prepared, which effectively improves the battery performance while improving the electrochemical reaction activity of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1These are scanning electron microscope and transmission electron microscope photographs of blank carbon nanofiber electrode materials ECNFs (a1, a2, a3) and highly active porous carbon nanofiber electrode materials GG-ECNFs (b1, b2, b3) prepared in Example 1.

[0024] Figure 2 The cyclic voltammetry curves of the front and back sides of the blank carbon nanofiber electrode material ECNFs and the highly active gradient porous carbon nanofiber electrode material GG-ECNFs prepared in Example 1 in vanadium electrolyte. The side with high graphite content is recorded as the front side (GGH-ECNFs), and the side without graphite is recorded as the back side (GG0-ECNFs).

[0025] Figure 3 The figures are the charge and discharge curves (a), capacity comparison (b), voltage efficiency and coulombic efficiency (c), energy efficiency diagram (d) and cycle stability curve diagram (e) of the symmetrical vanadium battery prepared in Example 2 at different current densities. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0027] Example 1

[0028] (I) Comparative example: blank carbon nanofiber electrode material (ECNFs)

[0029] The preparation method comprises the following steps:

[0030] 1) Preparation of blank electrospinning precursor solution

[0031] The dried polyacrylonitrile (PAN) powder with a molecular weight of 150,000 was dissolved in N,N,-dimethylformamide (DMF) and magnetically stirred at 80°C for 6 hours until completely dissolved to obtain a blank PAN / DMF electrospinning precursor solution with a polyacrylonitrile (PAN) mass percentage concentration of 14 wt%.

[0032] 2) Preparation of original blank polyacrylonitrile nanofiber material by electrospinning

[0033] The blank PAN / DMF electrospinning precursor solution is sucked into the syringe of the electrospinning device, and electrospinning is performed using the electrospinning technology to obtain the original blank polyacrylonitrile nanofiber material.

[0034] Electrospinning conditions: the stainless steel nozzle model is G20, the collector is a stainless steel roller, the roller speed is 100r / min; the voltage between the nozzle and the roller is 20kV; the distance between the nozzle and the roller is 12cm; the spinning temperature is 25℃; the spinning humidity is 30%RH; the push speed is 30μL / min, and the volume of the electrospinning precursor solution is 6mL.

[0035] 3) Preparation of blank carbon nanofiber electrode materials by pre-oxidation and carbonization

[0036] The obtained original blank polyacrylonitrile nanofiber material was flattened with a corundum plate and placed in a tube furnace for pre-oxidation treatment, i.e., heating to 290°C at a heating rate of 1°C / min in an air atmosphere and keeping the temperature for 60 min; then carbonization treatment was performed, i.e., heating at a rate of 5°C / min in a N2 atmosphere and keeping the temperature at 1000°C for 120 min, and then cooled to room temperature to obtain a blank carbon nanofiber electrode material, which was labeled as ECNFs.

[0037] like Figure 1 As shown in a1-a3, the diameter of the obtained blank carbon nanofiber electrode material is about 150 nm and the surface is smooth.

[0038] (II) Construction of highly active gradient porous carbon nanofiber electrode materials based on graphite microparticles

[0039] The preparation method comprises the following steps:

[0040] 1) Preparation of electrospinning precursor solution

[0041] The dried polyacrylonitrile (PAN) powder with a molecular weight of 150,000 and the spherical graphite microparticle powder with a diameter of 1 to 2 μm were dissolved in N,N,-dimethylformamide (DMF) in different proportions and magnetically stirred at 80°C for 6 hours until completely dissolved, and three electrospinning precursor solutions with different graphite microparticle contents were obtained, namely:

[0042] In the first electrospinning precursor solution, the mass percentage concentration of polyacrylonitrile (PAN) is 14%, and the mass percentage concentration of graphite microparticles is 0%.

[0043] In the second electrospinning precursor solution, the mass percentage concentration of polyacrylonitrile (PAN) is 14%, and the mass percentage concentration of graphite microparticles is 0.14%.

[0044] In the third electrospinning precursor solution, the mass percentage concentration of polyacrylonitrile (PAN) is 14%, and the mass percentage concentration of graphite microparticles is 1.4%.

[0045] 2) Preparation of original composite fiber materials by electrospinning

[0046] 2 mL of the first electrospinning precursor solution, 2 mL of the second electrospinning precursor solution and 2 mL of the third electrospinning precursor solution were sequentially sucked into the syringe of the electrospinning equipment. Using the electrospinning technology, the three electrospinning precursor solutions were continuously electrospun in order of graphite powder content to obtain the original nanofiber material with a gradient distribution of graphite microparticle content.

[0047] Electrospinning conditions: the stainless steel nozzle model is G20, the collector is a stainless steel roller, the roller speed is 100r / min; the voltage between the nozzle and the roller is 20kV; the distance between the nozzle and the roller is 12cm; the spinning temperature is 25℃; the spinning humidity is 30%RH; the push speed is 30μL / min, and 2mL of each of the three electrospinning precursor solutions is spun continuously.

[0048] 3) Pre-oxidation and carbonization preparation of highly active gradient porous carbon nanofiber electrode materials based on graphite microparticles

[0049] The original nanofiber material with a gradient distribution of graphite microparticle content was flattened with a corundum plate and placed in a tubular furnace for pre-oxidation treatment, i.e., heating to 290°C at a heating rate of 1°C / min in an air atmosphere and keeping warm for 60 minutes; then carbonization treatment was carried out, i.e., in a N2 atmosphere, heating at a rate of 5°C / min, keeping warm at 1000°C for 120 minutes, and then cooled to room temperature to obtain a high-activity gradient porous carbon nanofiber electrode material constructed based on graphite microparticles, labeled as GG-ECNFs.

[0050] like Figure 1 As shown in b1-b3, the diameter of the obtained high-activity gradient porous carbon nanofiber electrode material is about 200-400 nm, and the fiber surface is smooth.

[0051] Example 2 Electrochemical performance of highly active gradient porous carbon nanofiber electrode materials based on graphite microparticles

[0052] 1) Cyclic voltammetry test

[0053] Method: A three-electrode system was used, with 1 cm prepared in Example 1. 2 The blank carbon nanofiber electrode material and the highly active gradient porous carbon nanofiber electrode material based on graphite microparticles were used as working electrodes, saturated ganyl common electrode as reference electrode, platinum sheet as counter electrode, 0.1M VOSO4+2.0M H2SO4 as electrolyte, and the electrochemical performance of the electrodes was investigated by cyclic voltammetry at a scan rate of 5mV / s. The positive GGH-ECNFs (the side with more graphite content) and the reverse GG0-ECNFs (the side without graphite) of the highly active gradient porous carbon nanofiber electrode material based on graphite microparticles were contacted with the electrolyte for cyclic voltammetry tests.

[0054] like Figure 2 As shown, both ECNFs and GG-ECNFs electrodes showed V 2+ / V 3+ However, compared with ECNFs, the CV graphs measured on the front and back surfaces of the GG-ECNFs electrode have larger peak currents, which may be attributed to the fact that the gradient pore structure of the GG-ECNFs electrode material has a larger electroactive area, giving the electrode better electrocatalytic activity.

[0055] 2) Single battery charge and discharge test

[0056] Method: 1 cm prepared in Example 1 2 The blank carbon nanofiber electrode material and the highly active gradient porous carbon nanofiber electrode material based on graphite microparticles are used as positive and negative electrodes, wherein the side of the highly active gradient porous carbon nanofiber electrode material based on graphite microparticles, GGH-ECNFs, which contains more graphite particles, contacts the current collector, and the side of the GG0-ECNFs, which contains less graphite particles, contacts the separator. Nafion212 is an ion exchange membrane, 1.65MV 3+ / V 4+ +3.0M H2SO4 was used as the electrolyte, and a single cell was assembled and the charge and discharge test was performed. The charge and discharge cut-off voltages were 1.75V and 1V respectively, and the current density was 100mA / cm 2 ~400mA / cm 2 , the charge and discharge cycles were repeated 5 times at each current density.

[0057] The corresponding different electric density charge and discharge curves and capacity comparisons are as follows Figure 3 A and Figure 3 As shown in b, the battery efficiency is Figure 3 Medium c and Figure 3 In addition, the vanadium battery assembled with GG-ECNFs as positive and negative electrodes was tested for 370 cycles, and the corresponding battery efficiency decay is shown in Figure 3 Middle e.

[0058] like Figure 3 As shown in Figure d, the single cell using high-activity gradient porous carbon nanofiber electrode materials based on graphite microparticles as positive and negative electrodes shows higher energy efficiency at all current densities. As the current density increases, the difference in energy efficiency between the two becomes greater, indicating that the single cell using high-activity gradient porous carbon nanofiber electrode materials doped with graphite powder as positive and negative electrodes has better rate performance and cycle stability, which is due to the gradient pore structure of the electrode material, the larger electroactive area, and the stronger electrochemical reaction activity. At a current density of 200 mA / cm 2Under the condition of , the energy efficiency of the battery reached more than 80%. In addition, after 370 consecutive cycles of charge and discharge, the battery efficiency did not show obvious attenuation ( Figure 3 (e) further proves that the battery assembled with GG-ECNFs material has excellent cycling stability.

Claims

1. A method for constructing highly active gradient porous carbon nanofiber electrode materials based on graphite microparticles, It is characterized in that The method comprises the following steps: 1) three graphite microparticle powders of different masses are dispersed in a mixed solution of polyacrylonitrile PAN and N,N,-dimethylformamide DMF to obtain three electrospinning precursor solutions with different graphite microparticle contents; 2) electrospinning three electrospinning precursor solutions with different graphite microparticle contents continuously in the order of graphite microparticle contents from large to small or from small to large to obtain original nanofiber materials with a gradient distribution of graphite microparticle contents; 3) The obtained original nanofiber material with a gradient distribution of graphite microparticle content is flattened with a corundum plate, placed in a tubular furnace for pre-oxidation and carbonization treatment, and cooled to room temperature to obtain a high-activity gradient porous carbon nanofiber electrode material assembled from fiber layers with three different graphite microparticle contents.

2. The method according to claim 1, It is characterized in that In step 1), the diameter of the graphite microparticle powder is 1-2 μm, and the graphite microparticle contents of the three electrospinning precursor solutions with different graphite microparticle contents are 0%, 0.1-0.2% and 1-2% by mass respectively.

3. The method according to claim 1, It is characterized in that In step 1), the molecular weight of polyacrylonitrile PAN is 90,000 to 150,000, and the concentration of polyacrylonitrile PAN in the three electrospinning precursor solutions with different graphite microparticle contents is 10 to 20% by mass.

4. The method according to claim 1, It is characterized in that In step 2), the electrospinning conditions are as follows: the stainless steel nozzle model is G17~G22; the collector is a stainless steel roller, and the roller speed is 50~150r / min; the voltage between the nozzle and the roller is 19~22kV; the distance between the nozzle and the roller is 10~15cm; the spinning temperature is 25~35℃; the spinning humidity is 20~50%RH; the push speed is 20~40μL / min; the volume of each electrospinning precursor solution is 2~10mL.

5. The method according to claim 1, It is characterized in that In step 3), the pre-oxidation treatment conditions are: air atmosphere, heating rate of 1-5°C / min, pre-oxidation temperature of 260-320°C, and holding time of 30-120min.

6. The method according to claim 1, It is characterized in that In step 3), the carbonization treatment conditions are: under nitrogen or argon atmosphere, heating rate 1-5°C / min, carbonization temperature 900-1200°C, and holding time 60-180min.

7. Application of a highly active gradient porous carbon nanofiber electrode material based on graphite microparticles prepared by the method according to any one of claims 1 to 6 in an all-vanadium liquid flow battery.

8. The use according to claim 7, It is characterized in that The method is as follows: in a highly active gradient porous carbon nanofiber electrode material constructed based on graphite microparticles, a fiber layer with a high content of graphite microparticles is contacted with a current collector, and a fiber layer with a low content of graphite microparticles is contacted with a diaphragm to assemble an all-vanadium liquid flow battery.

9. The use according to claim 8, It is characterized in that The all-vanadium liquid flow battery has an electrolyte flow rate of 15 to 50 mL / min, a vanadium ion concentration of 1.0 to 1.7 M, and a sulfuric acid supporting electrolyte concentration of 2.0 to 3.0 M.

10. The use according to claim 8, It is characterized in that The current collector is a graphite composite conductive plastic plate, and the diaphragm is a nafion212 proton exchange membrane.

Citation Information

Cited By

  • Preparation method of carbon nanofiber rich in end face defect and application of carbon nanofiber in all-vanadium redox flow battery electrode material

    CN120443383A